COMPUTER HYDRODYNAMICS OF THE MELT AND POWDER CARBONIC MATERIALS MIXING IN BOWL - A. N. Chichko; N. V. Andrianov; S. V. erletskij; D. M. Kukuj; V. F. Sobolev; Ju. V. Jatskevich; O. I. Chichko (Литьë и металлургия)
The mathematical mechanism for modeling of the mixing processes of melts and powder materials, assumed as a basis of the out-of-furnace steel processing, is presented. The computer calculations of the melt speed fields, formed in the industrial bowl of the Belorussian metallurgical works, are given and analyzed.